4c-3=63

Simple and best practice solution for 4c-3=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c-3=63 equation:


Simplifying
4c + -3 = 63

Reorder the terms:
-3 + 4c = 63

Solving
-3 + 4c = 63

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 4c = 63 + 3

Combine like terms: -3 + 3 = 0
0 + 4c = 63 + 3
4c = 63 + 3

Combine like terms: 63 + 3 = 66
4c = 66

Divide each side by '4'.
c = 16.5

Simplifying
c = 16.5

See similar equations:

| 4p-20=10p-14 | | 9-(-3k+3)=(k+3)+3 | | 12x+28=48x-44 | | x=16x | | 2v-9=8-3v | | 4c-80=3c-51 | | 3x+4(2x-9)=-14 | | -9(v+2)+4v+6=8v+7 | | 1-5x-4x=-80 | | 3(2c-3)-3=4c+6 | | -5-8=121 | | 20x+49-2x=10x+2x | | [5x-9]=[7x+12] | | -5s-7.5-13.5s+15.6=0 | | 2+1.5(z+2)=3.5z-1 | | 1-5x-4x=80 | | 76-2x=101-7x | | -4d-6d=24 | | 18(x+45)=18(x+60) | | 2ry=5x+y | | 7x+3=x+13 | | -2=6(p-1)-4(3+p) | | 5(b+1)=2b+32 | | 2-4x=38 | | 5.3y+0.45=3.02y-2.04 | | 2x+49=-6x+97 | | (2x+4)(6x-8)= | | 8x+70=9x+69 | | 2y-6x=-3 | | 7K+3=K+13 | | 3y-4(-4y-18)=-118 | | 2/3+2=4/3+1/3 |

Equations solver categories